ASEAN and the law of the sea - Tangsubkul, Phiphat (Institute of Southeast Asian Studies, 1982)
The evolution of the Geo-Juridical nature of OCEAN space appropriation by coastal states and Asean states; Problems relating to jurisdiction and rights over living and non-living resources of Asean countries; Conclusion.